Innovative Methods to Improve the Learning: Addressing the Challenges of 21st Century Education (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Advance pedagogy is the way to enhance teaching and learning performance. Different innovative teaching methods are now in use across the globe. Hybrid teaching includes e - learning in addition to the face to face teaching. Use of technology and multimedia is described in details. Use of smart gadgets for different tasks like teaching, designing question papers, assessment of student, feedback and research methodology is discussed. The application of innovative teaching and learning methods is critical if we are to motivate and engender a spirit of learning as well as enthusiasm on the part of students, The role of education is to ensure that while academic staffs do teach, what is taught should also be intelligible to students emanating from culturally and linguistically diverse backgrounds and that they rapidly become familiar with the expected standards. It is more often than not the case that students underachieve because of the fact that they have not grasped an awareness of the level of assessment or what it is that the lecturer expects from them. Lecturers should thus apply themselves to utilizing innovative methods so that the students’ learning process is as free-flowing as possible and that the methodology they adopt is conducive to learning. Innovative teaching and learning methodologies such as short lecture, simulation, role-playing, portfolio development and problem-based learning (PBL) are very useful in addressing the rapid technological advances and developing workplaces that will be required in the foreseeable future.